PERTENTANGAN MISI KENABIAN DAN HUKUM PERNIKAHAN BEDA AGAMA DI INDONESIA: Analisis Faktor Penolakan dan Relevansinya - Sugitanata, Arif (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
The contradictions in the prophetic era over the noble mission also apply to marriage laws, especially the rules for interfaith marriages. The issue has been a long and unavoidable debate. This study seeks to answer the rejection factors and relevance of the contradiction between the prophetic mission and the law of interfaith marriage in Indonesia. Using a literature review methodology, which includes collecting relevant literature, mainly works still related to the research subject, then processed descriptively-analytically. The research suggests a correlation between the factors contributing to society's rejection of the prophetic treatise and the factors influencing Indonesian society's rejection of the interfaith marriage law. The significance lies in the mutual refusal shown by both parties, as they reject the benefits of the situation. Muslims and Indonesians alike have shown resistance to accepting the proposed benefits. On the other hand, it is also essential to recognize that a significant factor contributing to the rejection is a lack of understanding. Every individual must understand that the ideas brought by the prophets encompass genuine truths that require acceptance to safeguard earthly and afterlife existence, as well as the salvation of all humanity. Likewise, individuals in Indonesia need to understand the importance of the regulations about interfaith marriage.